Lignosus rhinocerotis extract ameliorates airway inflammation and remodelling via attenuation of TGF-β1 and Activin A in a prolonged induced allergic asthma model - Muhamad, Siti-Aminah; Safuan, Sabreena; Stanslas, Johnson; Wan Ahmad, Wan Amir Nizam; Mohd-Rosdan Bushra, Solehah; Bushra Nurul, Asma (Springer Science and Business Media LLC, 2023)
Allergic asthma is associated with chronic airway inflammation and progressive airway remodelling. The sclerotium of Lignosus rhinocerotis (Cooke) Ryvarden (Tiger Milk mushroom) is used traditionally to treat various illnesses, including asthma in Southeast Asia. This study was carried out to evaluate the effect of L. rhinocerotis extract (LRE) on airway inflammation and remodelling in a chronic model of asthma. The present study investigated the therapeutic effects of LRE on airway inflammation and remodelling in prolonged allergen challenged model in allergic asthma. Female Balb/C mice were sensitised using ovalbumin (OVA) on day 0 and 7, followed by OVA-challenged (3 times/week) for 2, 6 and 10 weeks. LRE (125, 250, 500 mg/kg) were administered by oral gavage one hour after every challenge. One group of mice were left untreated after the final challenge for two weeks. LRE suppressed inflammatory cells and Th2 cytokines (IL-4, IL-5 and IL-13) in BALF and reduced IgE level in the serum. LRE also attenuated eosinophils infiltration and goblet cell hyperplasia in the lung tissues; as well as ameliorated airway remodelling by reducing smooth muscle thickness and reducing the expressions of TGF-β1 and Activin A positive cell in the lung tissues. LRE attenuated airway inflammation and remodelling in the prolonged allergen challenge of allergic asthma model. These findings suggest the therapeutic potential of LRE as an alternative for the management of allergic asthma.